A multi-level analysis of public spending, growth and poverty reduction in Egypt - Fan, Shenggen; Al-Riffai, Perrihan; El-Said, Moataz; Yu, Bingxin; Kamaly, Ahmed (International Food Policy Research Institute, 2006)
Egypt is a lower middle-income country with a per capita gross domestic product (GDP) in 2003 of US$3,949 measured in international dollars, or purchasing power parity (World Bank 2005a). In the decade from 1975 to 1985, Egypt enjoyed rapid economic growth... however... Egypt still lags behind many middle-income countries in key social indicators. Further reforms are necessary to reduce poverty, especially if Egypt is to achieve the United Nations’ Millennium Development Goal (MDG) of halving the number of poor between 1990 and 2015. Government expenditures are an important means of promoting economic growth, reducing poverty, and improving income distribution... The overarching objective of this report is to use a multi-level analysis approach to assess both the effects of various government expenditures on growth and poverty reduction and the trade-offs between these two goals in order to determine policy options toward the achievement of the MDGs. The study involves analyses and simulations at household, sectoral, and regional levels, and at macro-levels using alternative analytical tools. While the analyses at each level were carried out independently, the report provides a synergy of the findings... The report concludes with a synthesis of the different levels of analysis.